Parthenium hysterophorus alleviates wilt stress in tomato plants caused by Ralstonia solanacearum through direct antibacterial effect and indirect upregulation of host resistance - Najeeb, Saba; Li, Yan (Frontiers in Plant Science, 2023)
Heavy damage to tomato crops due to wilt stress caused by the pathogenic bacterium Ralstonia solanacearum and the insufficient availability of management strategies with desired control levels urged the researchers to investigate more reliable control methods to manage this issue in tomato and other horticultural crops. In this study, Parthenium hysterophorus, a locally and freely available herbaceous plant, was successfully used to manage bacterial wilt of tomatoes. The significant growth reduction ability of P. hysterophorus leaf extract was recorded in an agar well diffusion test and its ability to severally damage the bacterial cells was confirmed in SEM analysis. In both greenhouse and field trials, soil amended with P. hysterophorus leaf powder at 25 g/kg soil was found to effectively suppress the pathogen population in soil and significantly reduce the wilt severity on tomato plants, resulting in increased growth and yield of tomato plants. P. hysterophorus leaf powder at concentrations greater than 25 g/kg soil caused phytotoxicity in tomato plants. The results showed that P. hysterophorus powder applied through the mixing of soil for a longer period of time before transplanting tomato plants was more effective than mulching application and a shorter period of transplantation. Finally, the indirect effect of P. hysterophorus powder in managing bacterial wilt stress was evaluated using expression analysis of two resistance-related genes, PR2 and TPX. The upregulation of these two resistance-related genes was recorded by the soil application of P. hysterophorus powder. The findings of this study revealed the direct and indirect action mechanisms of P. hysterophorus powder applied to the soil for the management of bacterial wilting stress in tomato plants and provided the basis for including this technique as a safe and effective management strategy in an integrated disease management package.